Financial Statement Analysis of Cement Industry Companies with Dupont System Method to Performance Measurement Periode 2018-2021 - Riduwan Maliki; Dwi Agus Arvianto (P2M Politeknik Pertanian Negeri Samarinda, 2023)
The purpose of this study was to evaluate the financial performance of cement industry companies in Indonesia which includes four companies namely SMCB, SMGR, INTP, and SMBR for the 2018-2021 period using the Dupont system method considering the analysis of the Covid-19 pandemic. Descriptive-quantitative analysis and the DuPont system method were used as analytical methods. The data used in this study comes from the annual reports of four companies listed on the Indonesia Stock Exchange. The results show that the Covid-19 pandemic had a significant impact on the financial performance of companies in the cement industry, especially in terms of profitability and use of funds. These factors can affect the company's financial performance during the Covid-19 pandemic, so management must pay attention to these factors to improve the company's financial performance. This study can help investors and stakeholders understand the impact of the Covid-19 pandemic on the financial performance of companies in the cement industry in Indonesia and can provide information to companies about the challenges they are facing during the pandemic. In addition, the analysis of the Dupont system method also shows that factors such as net profit margins, asset efficiency, and financial leverage affect the financial performance of companies in the cement industry. The results of this study can be used as a basis for improving the company's financial performance in the future by optimizing these factors.